How have youth with Autism Spectrum Disorder managed quarantine derived from COVID-19 pandemic? An approach to families perspectives - Mumbardó-Adam, Cristina; Barnet-López, Silvia; Balboni, Giulia (Research in developmental disabilities, 2021)
•Youth with ASD have unique support needs during COVID-19 quarantine.•Quarantine has not always propitiated higher levels of anxiety in youth with ASD.•Families beneficiated of additional time with their offspring during quarantine.•Building positive contexts for youth with ASD and their families are recommended. Quarantine derived from COVID-19 pandemic has challenged children and adolescents with Autism Spectrum Disorder (ASD) and their families daily life and routines. Because of these children unique needs related to manage uncertainty and overcoming situations, an in-depth approach to how they navigated through quarantine urged to better comprehend their current support needs. Forty-seven families with a child with ASD ranging in age between 2 and 17 years old (M = 7.3, SD = 3.4) from the north of Spain responded to an online developed questionnaire on different aspects of their daily life management of quarantine. Most of the families stressed that their offspring better drove quarantine than expected. Some families reported that youth participated more often in families’ routines and were more communicative with their parents. Families, beyond some difficulties aroused, had more time to qualitatively spend with their children to teach new skills as autonomy or house care related skills. Families also developed new strategies to manage quarantine, such as structuring their days, using visual supports or new technologies for learning or leisure, and found more useful in this effort their family cohesion, online contact with relatives, and having online psychological supports.